On AlO Emission Spectroscopy as a Diagnostic in Energetic Materials Testing. Issue 4 (11th February 2013) - Peuker, Jennifer Mott; Lynch, Patrick; Krier, Herman; Glumac, Nick
Abstract The emission of AlO is commonly observed in tests involving aluminum combustion in propellants and explosives. Such emission has been used as a signature of combustion, as a tool for measuring ignition and reaction times, and as a thermometer. This paper provides a critical review of methodologies exploiting AlO emission spectroscopy as a quantitative tool in energetics testing. Controlled tests involving aluminized explosives, as well as those using added alumina, are conducted, in which AlO emission is quantified and compared to total oxidation in the final residue. Experimental parameters such as optical depth and fireball confinement are systematically varied to examine the effect on AlO emission. We find that thermometry using AlO remains valid, and a new approach to using low resolution spectra is proposed. However, AlO emission spectroscopy or photometry can be quantitatively correlated to ignition and burning time, or used to infer the presence or absence of aluminum combustion, only under a limited set of circumstances. Factors that limit the ability to use AlO emission quantitatively are discussed in depth.